Treatment of Arterial Ischemic Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Current guidelines and evidence in the treatment of childhood arterial ischemic stroke (AIS) are reviewed by researchers at The Children's Hospital, Denver, CO, and other centers.